A rare case of unilateral psoriatic arthritis of the left temporomandibular joint: MRI and CBCT findings - Oana Almasan; Raluca Roman; Ioan Morosan; Mihaela Hedesiu (Romanian Journal of Stomatology, 2022)
Psoriatic arthritis (PsA) of the temporomandibular joint (TMJ) is a rare type of inflammatory arthritis. We present a 21-year-old male diagnosed with psoriasis six years ago. Inflammatory autoimmune arthritis was diagnosed. TMJ involvement comprised arthralgia, degenerative joint disease, joint pain, limited range of jaw movements, and crepitus. Biomarkers revealed a C-reactive protein of 0.14 mg/L and seronegative inflammation with negative rheumatoid factor. At imaging important left condyle morphology derangements with erosions, decreased subchondral bone fat signal, condyle edema, osteophytes, and periosteal apposition, and loss of the normal disk position and morphology were present. The particularity of this case is given by the rapid onset of psoriasis arthritis with negative rheumatoid factor in a young male and juxta-articular new bone formation. The treatment plan comprised anti-inflammatory drugs, methotrexate, and folic acid, aimed for the general disease, and an occlusal splint, aiming for the relief of the TMJ symptoms.